Anthocyanins acylated with gallic acid from chenille plant, Acalypha hispida - Reiersen, Bergitte; Kiremire, Bernard T; Byamukama, Robert; Andersen, Øyvind M. (Phytochemistry, 2003)
Three anthocyanins were isolated from the red flowers of chenille plant, Acalypha hispida Burm. (Euphorbiaceae) by a combination of chromatographic techniques. Their structures were elucidated mainly by homo- and heteronuclear nuclear magnetic resonance spectroscopy and electrospray mass spectrometry, and supported with complete assignments of 13C NMR resonances. The novel pigment, cyanidin 3-O-(200-galloyl-600-O-a-rhamnopyranosyl-b-galactopyranoside) (5%), contains the disaccharide robinoside. The other anthocyanins were identified as cyanidin 3-O-(200-galloyl-b-galactopyranoside) (85%), and cyanidin 3-O-b-galactopyranoside (5%). Anthocyanins acylated with gallic acid have previously been identified in species from the families Nymphaeaceae and Aceraceae, and tentatively in Abrus precatorius (Leguminosae).
Keywords: Acalypha hispida; Euphorbiaceae; Flowers; Anthocyanins; Robinoside; Cyanidin 3-O-